(untitled) - Holliday, Adrian (London,New York, 2004)
Routledge Applied Linguisticsis a series of comprehensive resource books, providing students and researchers with the support they need for advanced study in the core areas of English language and Applied Linguistics.Each book in the series guides readers through three main sections, enabling them to explore and develop major themes within the discipline.Section A, Introduction, establishes the key terms and concepts, and extends readers' techniques of analysis through practical application.Section B, Extension, brings together influential articles, sets them in context, and discusses their contribution to the field.Section C, Exploration, builds on knowledge gained in the first two sections, setting thoughtful tasks around further illustrative material.This enables readers to engage more actively with the subject matter and encourages them to develop their own research responses. Throughout the book, topics are revisited, extended, interwoven and deconstructed, with the reader's understanding strengthened by tasks and follow-up questions.Intercultural Communication:* introduces the key theories of intercultural communication* explores ways in which people communicate within and across social groups* is built around three themes - identity, otherization and representation - which are followed and developed over the book's three sections* gathers together influential readings from key names in the discipline, including: James Paul Gee, James P. Lantolf, Les Back, Richard Dyer, Jacques Derrida and Alastair Pennycook.Written by experienced teachers and researchers in the field, Intercultural Communicationis an essential resource for students and researchers of English language and Applied Linguistics.
Keywords: Intercultural communication,Conflict management,Multiculturalism,Pluralism (social sciences),Diversity in the workplace; Problems, exercises, etc.,Problems, exercises, etc.,Management; United States,United States,United States